2018
DOI: 10.25077/ar.5.2.81-93.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Framework of Cooperative Problem-based Learning (Co-PBL) to Promote Verbal Creativity in EFL Writing: Is It Feasible?

Abstract: One of the influential factors that could affect students’ writing skill is verbal creativity (VC). As an attempt to promote VC in EFL writing, two learning models i.e. cooperative learning and problem-based learning are incorporated and modified. This study was aimed at: (1) describing the structure of the framework of Co-PBL in order to promote VC in EFL writing; and (2) evaluating the feasibility of the framework of Co-PBL in EFL writing class. To achieve the goals of this study, a descriptive explanatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The main barriers related to the tutor identified were lack of motivation, lack of experience and training, tutors with clinical orientation, and tutors focused primarily on evaluation. Similar findings were identified in studies conducted in Ethiopia, Azerbaijan, Indonesia, Pakistan and Korea [ 21 25 ]. This is likely due to the fact that many tutors graduated from traditional teacher-centered curricula and lack the experience and skills needed to effectively facilitate and evaluate problem-based learning (PBL).…”
Section: Discussionsupporting
confidence: 90%
“…The main barriers related to the tutor identified were lack of motivation, lack of experience and training, tutors with clinical orientation, and tutors focused primarily on evaluation. Similar findings were identified in studies conducted in Ethiopia, Azerbaijan, Indonesia, Pakistan and Korea [ 21 25 ]. This is likely due to the fact that many tutors graduated from traditional teacher-centered curricula and lack the experience and skills needed to effectively facilitate and evaluate problem-based learning (PBL).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the internalization of problem-based learning activities also encouraged Indonesian EFL learners to scaffold other learners' developing learning levels in a better purpose, establish more positive social interactions with other learning members upholding distinctive learning perspective, magnify their self-confidence, and liven up their learning responsibility within L2 productive language learning surroundings. All of these valuable writing learning merits are closely intertwined with the prior research findings uncovered by Ghufron and Ermawati (2018) averring that Indonesian EFL learners will be more adept in cultivating their social, problem-solving, and critical thinking skills beneficial to raise their self-confidence along with learning responsibility in acquiring the targeted L2 writing skills. In another identical study, Jumariati and Sulistyo (2017) found out that the major influential writing learning impact imparted by problem-based learning activities allow Indonesian EFL learners to be more collaborative, creative, and confident L2 writers while producing the targeted writing products.…”
Section: Findings and Discussionmentioning
confidence: 72%
“…In a similar vein, Wiliyanti (2015) discovered that problem-based learning enterprises make Indonesian EFL learners become more life-long L2 academicians eager to foster their productive language skills more vehemently amid varied taxing learning challenges. Affandi and Sukyadi (2016); Dharma and Adiwijaya (2018); Ghufron and Ermawati (2018); Jumariati and Sulistyo (2017); Nurhayati et al, (2019); Palupi et al, 2020); Praba et al, (2018); Toba et al, (2019); Wachyu and Rukmini (2015); Yuliani (2017); Yusuf (2010).…”
Section: Findings and Discussionmentioning
confidence: 99%